O ensino e a aprendizagem do gênero textual redação do Enem: os mecanismos enunciativos na construção da autoria na argumentação - Calabria, Victor Flávio Sampaio (2020)
This thesis aims to analyze the construction of authorship in the essay-argumentative texts produced by students of the third year of a public high school, through the context of production, the voices and modalizations and the argumentative action that guide the gender learning scene textual study. Certainly, when we are analyzing the path of construction of authorship in these texts, such investigation allows relevant reflections to be made around the working conditions of the teacher, the production conditions of the students and around the prescriptive texts that underlie such school productions. Thus, we are inserted in the database researches focused on the teaching and learning of the mother language, specially anchored in Applied Linguistics, and we consider the theoretical and methodological stage assumptions of Sociodiscursive Interactionism (BRONCKART, 2012), regarding teaching and the analysis of the text as an empirical product of the language activity, articulating the enunciative mechanisms, as linguistic elements that contribute to the pragmatic coherence of the text, and the evidence of authorship, as presented by Possenti (2002). Referring the methodological aspects, our research has a qualitative approach (MINAYO, 2013) and, as for the procedures, it is characterized as an action research (THIOLLENT, 2011). The data, according to the objectives, they were divided into two groups: a) preliminary data and; b) outcome data. These data are composed by elements that contextualize the teaching process mediated by the didactic sequence (SCHNEUWLY and DOLZ, 2004) and its stages, as well as the empirical texts produced by students at different times in the teaching process. The results confirm the importance of the teaching and school process as spaces for the development of argumentative action in the most varied discursive practices and for the construction of authorship, however, such practices must break the school walls and the curricular rigidity of the disciplines. Regarding their voices, we noticed some difficulty of the students in mobilizing other enunciators in order to give greater argumentative support to their personal point of view, making the voice of the empirical author more evident, even if mobilized in theoretical discourse, as required by the textual genre. Concerning the modalizations, it is possible to identify them in different parts of the text, with pragmatic and deontic modalities having a higher productivity in intervention proposals, in general, located in the conclusions of the analyzed texts.